SARS-CoV-2 seroprevalence and seroconversion in Finnish households with school-aged children between June 2020 and April 2022 - Ahti, Jaakko; Ollila, Helena; Toivonen, Laura; Salo-Tuominen, Krista; Ivaska, Lauri; Julkunen, Ilkka; Peltola, Ville (Informa Healthcare, 2026)
Background
SARS-CoV-2 spreads efficiently in households with children. Here, we aimed to examine whether serological methods, in addition to PCR, can improve understanding of SARS-CoV-2 transmission within households.
Methods
Within the prospective birth-cohort study called the STEPS Study, 175 households with 376 children and 324 adults were prospectively followed for acute respiratory infections from June 2020 to April 2022. SARS-CoV-2 was tested by PCR and antigen tests. IgG antibodies against SARS-CoV-2 nucleoprotein (N) and spike (S) proteins were determined at recruitment and at two later timepoints to assess seroprevalence, and five weeks after a PCR-positive infection in the household to assess seroconversion. Secondary attack rates (SARs) based on seroconversion or PCR-positivity were calculated and compared among index and secondary cases.
Results
SARS-CoV-2 anti-N-IgG seroprevalence showed a minor increase from 0.5% at recruitment, starting in June 2020, to1.9% at the last serum collection. SARS-CoV-2 RNA was detected by PCR in altogether 334 (48%) participants. The SAR for the adult index cases was higher than the SAR for the child index cases (77% vs 48%; p = 0.0027). The SARs were similar for unvaccinated (0–1 vaccinations) and vaccinated (2–3 vaccinations) index cases (53% and 63%, respectively; p = 0.28), but the SAR for unvaccinated secondary cases was higher compared to the SAR for vaccinated secondary cases (83% vs 52%; p = 0.0067).
Conclusion
In this study, adults spread SARS-CoV-2 in households more efficiently than children. While the index case vaccination status showed no difference, unvaccinated household members were more prone to SARS-CoV-2 infection than vaccinated individuals.
Key points
A cohort of households with children was prospectively studied for SARS-CoV-2 transmission through repeated PCR, and serology was obtained 5 weeks post-infection. Adults transmitted the virus more effectively than children, and unvaccinated participants were more susceptible than vaccinated participants.
Keywords: children, COVID-19, household transmission, SARS-CoV-2, secondary attack rate, seroconversion, serology